Fresh groundwater discharge insignificant for the world’s oceans but important for coastal ecosystems - Luijendijk, Elco (Nat Commun, 2020)
The flow of fresh groundwater may provide substantial inputs of nutrients and solutes to the oceans. However, the extent to which hydrogeological parameters control groundwater flow to the world’s oceans has not been quantified systematically. Here we present a spatially resolved global model of coastal groundwater discharge to show that the contribution of fresh groundwater accounts for ~0.6% (0.004%–1.3%) of the total freshwater input and ~2% (0.003%–7.7%) of the solute input for carbon, nitrogen, silica and strontium. However, the coastal discharge of fresh groundwater and nutrients displays a high spatial variability and for an estimated 26% (0.4%–39%) of the world’s estuaries, 17% (0.3%–31%) of the salt marshes and 14% (0.1–26%) of the coral reefs, the flux of terrestrial groundwater exceeds 25% of the river flux and poses a risk for pollution and eutrophication.